Preaching the Word of God in the Polish synodal synthesis - Leszek Szewczyk (Polonia Sacra)
Launched in the Catholic Church by Pope Francis on October 10, 2021, the Synod on Synodality is entering the next stages. Continental syntheses have already been published, preceded by diocesan and national syntheses. The nationwide synodal synthesis and individual diocesan surveys are valuable sources containing numerous opinions on the state of preaching the Word of God in Poland. Despite the noticeable lack of theological references, Polish syntheses are important for the theory and practice of preaching the Word of God. The syntheses were prepared based on the opinions of 65,000 people participating in parish and diocesan meetings and 42 thousand people who responded to surveys and written correspondence. This study aimed to extract from the syntheses mentioned above issues concerning the nature of the homily and its position in the liturgy, the preacher of the Word of God, the general assessment of preaching in Poland, as well as the assessment of the content and form of homily preaching. However, the opinions and proposals contained in the syntheses should be the subject of further, in-depth research in the theology of preaching the Word of God.